Bilingualism: the two languages of young people in care - Kim Snow (Scottish Journal of Residential Child Care)
Institutions create their own languages, which become embedded in everyday experience (van Dijk, 1995). In order to function successfully, those in the subordinate position in the institution must learn the language of the institution. Residential child care is one such institution. Institutions and institutional language can be understood on the micro scale of a foster home or a group home or on the macro level of societal relations (Smith, 1999). Those in a less powerful position (i.e. young people in residential care) have no choice but to learn the language of the more powerful (Freire, 1985). Those in a position of authority (i.e. staff within the institutions) could choose to learn the language of the young people who occupy as less powerful position; however, they have no need to do so. Many examples of this can be cited, such as those of bilingual French Canadians as compared to unilingual English Canadians, bilingual Palestinians living in Israel as compared to unilingual Israelis, or even children in care as compared to